Control of electron transfer between Ce3+ and Cr3+ in the Y3Al5−xGaxO12 host via conduction band engineering1. Issue 22 (14th June 2015) - Ueda, Jumpei; Dorenbos, Pieter; Bos, Adrie J. J.; Kuroishi, Keisuke; Tanabe, Setsuhisa
<x xml:space="preserve">Abstract</x> Charging efficiency by blue light and trap depth were controlled via conduction band engineering in Y3Al5−xGaxO12:Ce3+–Cr3+.